ChemInform Abstract: Light‐Induced Structural Changes in (HgBr2)3(As4S4)2: An X‐Ray Single‐Crystal Diffraction, Raman Spectroscopy and ab initio Study. Issue 44 (14th October 2013) - Zoppi, M.; Bindi, L.; Roedl, T.; Pielnhofer, F.; Weihrich, R.; Pfitzner, A.; Bonazzi, P.
Abstract The response to light exposure of the As4S4 molecule within the structure of (HgBr2)3(As4S4)2 (space group P21/c, Z = 2) is investigated by single crystal XRD, Raman spectroscopy, and relativistic DFT‐GGA band structure calculations.